2009
DOI: 10.1186/1471-2164-10-451
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the central nervous system of the mollusc Lymnaea stagnalis

Abstract: Background: The freshwater snail Lymnaea stagnalis (L. stagnalis) has served as a successful model for studies in the field of Neuroscience. However, a serious drawback in the molecular analysis of the nervous system of L. stagnalis has been the lack of large-scale genomic or neuronal transcriptome information, thereby limiting the use of this unique model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 46 publications
1
76
1
Order By: Relevance
“…As just one example, we hypothesized that the reduction in [Ca 2ϩ ] i may have subsequently reduced activation of K Ca channels. Transcriptome analysis of the Lymnaea central nervous system (CNS) has revealed the presence of K Ca channels (Feng et al 2009), although we did not confirm their presence in the VF neurons. Regardless, we found that application of the small-conductance K Ca (SK) channel blocker, apamin, did not mimic any of the effects of RA, and thus our data did not support any role for this particular channel in the electrophysiological changes induced by RA.…”
Section: Discussioncontrasting
confidence: 57%
“…As just one example, we hypothesized that the reduction in [Ca 2ϩ ] i may have subsequently reduced activation of K Ca channels. Transcriptome analysis of the Lymnaea central nervous system (CNS) has revealed the presence of K Ca channels (Feng et al 2009), although we did not confirm their presence in the VF neurons. Regardless, we found that application of the small-conductance K Ca (SK) channel blocker, apamin, did not mimic any of the effects of RA, and thus our data did not support any role for this particular channel in the electrophysiological changes induced by RA.…”
Section: Discussioncontrasting
confidence: 57%
“…Thus, L. stagnalis may represent a very good candidate because, as we have shown here, it expresses a sleeplike state in adulthood, yet is simple enough to facilitate neurophysiological experimentation at the cellular level (Mills and Winlow, 1979;Lukowiak et al, 2003). Its potential value as a simple animal model of sleep is enhanced by recent and ongoing genome analysis in this species (Feng et al, 2009). The cessation of locomotor activity and rasping movements of the radula, the partial retraction of the tentacles and the reduction in the aspect ratio of the foot all suggest that quiescence involves a general suppression of motor output in Lymnaea.…”
Section: Discussionmentioning
confidence: 79%
“…Reaching densities of 5,000 mm À2 in some regions, there were hundreds to tens of thousands of each of multiple PSC types per CSO. Thus, the total number of PSCs in all four CSOs almost certainly dwarfs the $20,000 neurons present in the entire CNS (Feng et al, 2009). These results make it clear that understanding the neural basis of behavior in L. stagnalis and other gastropods needs to be extended to include this massive, but relatively ignored portion of the nervous system.…”
Section: Discussionmentioning
confidence: 97%